THE SOCIAL SIGNIFICANCE OF ENTREPRENEURIAL ACTIVITY - Ravshanova Ziyoda Nuraliyevna (Galaxy International Interdisciplinary Research Journal, 2021)
The current stage of economic reforms in Uzbekistan is characterized by the development of small business and private entrepreneurship, giving it broad economic freedom. In this regard, the definition of measures to counter the risks of the global financial and economic crisis, the prevention and combating of any negative consequences of this crisis that may affect the economy of our country, "Anti-Crisis Program for 2009-2012" Ensuring the successful implementation of the tasks set out in the Constitution is a priority for all of us today.